Excessive distribution of quantum entanglement - Zuppardo, Margherita (2016)
We classify entanglement distribution protocols based on whether or not entanglement gain is observed with respect to communicated and initial entanglement. We call a protocol nonexcessive if the gain of entanglement is bounded by the communicated entanglement and excessive if it violates this bound. We present examples of excessive protocols that achieve significant gain, independently of the presence of the initial and (or) communicated entanglement. We show that, for certain entanglement measures, excessive entanglement distribution is possible even with pure states, which sheds light on the possibility of formulating a unifying approach to quantifiers of quantum correlations. We point out a “catalytic” effect, where a protocol is turned into an excessive one by sending an intermediate particle (which does not change the initial entanglement) in advance of the designated carrier. Finally, we analyze the protocols in noisy scenarios and show that, under suitable conditions, excessive distribution may be the only way to achieve entanglement gain.